2002
DOI: 10.1046/j.1365-2559.2003.01530.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mucins (MUC1, MUC2, MUC5AC and MUC6) in mucinous carcinoma of the breast: comparison with invasive ductal carcinoma

Abstract: The expression rate of MUC1/CORE and MUC1/HMFG-1, which is related to poor prognosis in the gastric and colorectal cancers, is low in mucinous carcinomas. The high expression rate of gel-forming secretory mucins (MUC2 and MUC6) in mucinous carcinoma suggests that high production of these types of mucins may act as a barrier to cancerous extension resulting in their less aggressive biological behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
119
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(132 citation statements)
references
References 36 publications
11
119
0
2
Order By: Relevance
“…The high level of the gel-forming MUC2 mucin in breast cancer may act as a barrier that interferes with extension of the malignant cells, an advantage that may explain the less aggressive behaviour of mucinous carcinoma of the breast. 23 We also found a significantly more frequent ERnegative phenotype among MUC2-positive nonmucinous tumours compared with the negative tumours. This can be explained by the relatively higher incidence of grade 3 tumours compared with grade 1 and 2 (55.8% vs 14.4 and 29.85%, respectively), which agrees with a previous study stating that MUC2 overexpression by invasive ductal carcinomas is associated with aggressive tumour behaviour.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…The high level of the gel-forming MUC2 mucin in breast cancer may act as a barrier that interferes with extension of the malignant cells, an advantage that may explain the less aggressive behaviour of mucinous carcinoma of the breast. 23 We also found a significantly more frequent ERnegative phenotype among MUC2-positive nonmucinous tumours compared with the negative tumours. This can be explained by the relatively higher incidence of grade 3 tumours compared with grade 1 and 2 (55.8% vs 14.4 and 29.85%, respectively), which agrees with a previous study stating that MUC2 overexpression by invasive ductal carcinomas is associated with aggressive tumour behaviour.…”
Section: Discussionsupporting
confidence: 56%
“…[49][50][51] In our series, MUC2 was expressed with a very high frequency in mucinous carcinomas compared with other tumour types as previously reported. 23,30,52 A previous study has described MUC2 expression in the adjacent in situ lesions as well as adjacent and remote normal breast tissue and suggested that altered MUC2 expression pattern existing in normal breast tissue is a directional vector in histogenesis of such histological tumour type. 52 However, in this study, we could not confirm An inverse association has been identified between those tumours, excluding mucinous carcinomas, expressing MUC2 and nodal spread and vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mucin secreted has been found to be positive for MUC 2 and low level of MUC 1 14 . A very small proportion (<5%) of Mucinous carcinoma has been showing positivity for MUC 5 15 . There is one study which has described endocrine differentiation of mucinous carcinoma of breast 16 .…”
Section: Case Report Discussionmentioning
confidence: 99%